Analysis of Chlorophyll Content and Vegetative Growth of Land Kale (Ipomea reptans P.) Due to NPK Fertilizer and Bokashi Fertilizer Treatment - Azzahra, Fatima; Raksun, Ahmad; Mertha, I Gde (Jurnal Biologi Tropis, 2025)
Land kale (Ipomea reptans P.) is a popular leafy vegetable in Indonesia due to its fast growth and high nutritional value. Its productivity relies heavily on the proper application of fertilizer. This study investigates the effects of NPK fertilizer, Bokashi fertilizer, and their combination on land kale's vegetative growth and chlorophyll content. Conducted from May to July 2025 at the Faculty of Agriculture, University of Mataram's greenhouse, the experiment employed a Completely Randomized Design (CRD) with two factors: five levels of NPK fertilizer (0–2 gr/100 ml water) and five levels of Bokashi fertilizer (0–400 gr/polybag). Growth parameters measured included plant height, number of leaves, stem diameter, fresh weight, dry weight, and chlorophyll content. Data analysis involved two-way ANOVA and Duncan’s Multiple Range Test (DMRT). Results indicated NPK fertilizer significantly affected all growth parameters and chlorophyll content, while Bokashi fertilizer significantly influenced stem diameter, fresh weight, and dry weight, but not plant height, leaf number, and chlorophyll content. The interaction between NPK and Bokashi fertilizers significantly impacted plant height, fresh weight, and dry weight, though it had no significant effect on leaf number, stem diameter, and chlorophyll content.